Competency-Based Curriculum Reform in Germany - Lukas Schneider (CV Edujavare Publishing, 2025)
Competency-based curriculum reform has fundamentally reshaped German higher education since the Bologna Process, shifting educational paradigms from content-centred knowledge transmission to outcome-oriented competence development. This study examines the implementation, challenges, and outcomes of competency-based curriculum reform across German universities and universities of applied sciences, drawing upon national policy frameworks, institutional case studies, and empirical evidence from teacher training and vocational education contexts. Germany's approach is distinguished by the 2005 Qualifications Framework for German Higher Education Degrees, the integration of the European Qualifications Framework, and the systematic embedding of competence orientation within modularised study programmes. The research identifies four critical dimensions of reform: the formulation of learning outcomes at programme, module, and course levels; the transformation of teaching methods toward student-centred, action-oriented pedagogies; the development of competence-based assessment formats; and the alignment of accreditation procedures with competency criteria. Findings indicate that while formal compliance with competence orientation has been widely achieved, substantive implementation of the associated didactic transformations remains uneven across disciplines and institutions. Persistent challenges include the tension between academic scientific training and professional employability, the difficulty of assessing complex competences through traditional examination formats, and the gap between intended curriculum designs and enacted classroom practices. The study concludes that sustainable competency-based reform requires sustained investment in faculty development, systematic approaches to competence progression across study programmes, and institutional cultures that value educational innovation alongside research excellence. These insights contribute to the broader European discourse on the Bologna Process and offer actionable recommendations for higher education systems navigating similar transitions.